Birthing Balls in Modern Obstetrics: A Systematic Review of Benefits and Challenges - Thenesha.k; Dr.Vasantha.S (The Bioscan, 2024)
Background: Birthing balls, also known as exercise balls, are becoming a popular non-pharmacological intervention in modern obstetrics. They are believed to offer numerous benefits during labor, such as reducing pain, enhancing maternal comfort, and potentially shortening labor duration. However, there is a need for a comprehensive review of the available evidence to better understand their efficacy and any associated challenges. Objective: This systematic review aims to evaluate the benefits and challenges of using birthing balls in obstetrics, focusing on their impact on labor outcomes, maternal comfort, and any potential risks. Methods: A systematic search of electronic databases, including PubMed, Cochrane Library, MEDLINE, and CINAHL, was conducted to identify studies on birthing ball use in obstetrics. The review included randomized controlled trials (RCTs), observational studies, and reviews published in English from January 2000 to December 2023. The quality of the studies was assessed using the Cochrane Risk of Bias tool and the Newcastle-Ottawa Scale. Results: The review of 25 studies, comprising 15 randomized controlled trials and 10 observational studies, found that birthing balls significantly reduced the duration of the first stage of labor and effectively managed labor pain. Women using birthing balls reported greater comfort and satisfaction due to enhanced mobility and the adoption of upright positions during labor. While the impact on cesarean section rates was mixed, birthing balls were shown to promote optimal fetal positioning. Conclusion: Birthing balls offer significant benefits in obstetric care, particularly in reducing labor duration and enhancing maternal comfort.